Isolation and Antibiogram of Clostridium tetani from Clinically Diagnosed Tetanus Patients - Hanif, Hajra (Am J Trop Med Hyg, 2015)
Clostridium tetani, the etiologic agent of tetanus, produces a toxin that causes spastic paralysis in humans and other vertebrates. This study was aimed for isolation, identification, and determination of antimicrobial susceptibility of C. tetani from clinically diagnosed tetanus patients. Isolation was done from deep-punctured tissues of the foot and arm injuries of 80 clinically diagnosed tetanus patients from the Pakistan Institute of Medical Sciences hospital. We successfully screened out five C. tetani isolates out of 80 samples based on the strain-specific characteristics confirmed through biochemical testing and toxin production. A disc diffusion method was used for antimicrobial susceptibilities and C. tetani isolates showed susceptibility to cefoperazone, chloramphenicol, metronidazole, penicillin G, and tetracycline, but were found to be resistant to erythromycin and ofloxacin. During animal testing, all the infected mice developed symptoms of tetanus. The results showed that identification of C. tetani is possible using biochemical and molecular tools and that the strains of C. tetani isolated had not developed resistance against the antibiotics most often used for the treatment of tetanus.